Surgical and Molecular Evaluation of Pediatric Hydatid Cyst Cases in Eastern Turkey - Bakal, Unal; Simsek, Sami; Kazez, Ahmet (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2015)
Cystic echinococcosis (CE) caused by Echinococcus granulosus is a major public health problem worldwide, including Turkey. The aim of the current study was to identify the strains and to estimate the potential risk factors of E. granulosus in operated pediatric cases in eastern Turkey. Ten pediatric patients (7 boys and 3 girls) living in rural areas, with ages ranging from 3 to 15 years old and various clinical histories, were included in this study. Eight patients had only liver hydatid cyst, while 1 patient had liver and lung hydatid cyst and the other liver, lung, and spleen, together. There were 2 ruptured liver cysts. After surgery, during follow-up, no increase was observed in hemagglutination levels, there were no mortalities, and there was no evidence of recurrence at 2 years post operation in all patients. Molecular analysis was performed on hydatid cyst samples obtained from the 10 pediatric cases. According to mt-12S rRNA PCR results, all cases were found to be G1/G3 cluster of E. granulosus sensu stricto.
Keywords: Hydatid cyst; pediatric surgery; risk factor; PCR; Turkey